NAVIGATING THE INTERSECTION NEURO-MARKETING AND CONSUMER BAHAVIOR ANALYSIS: LEVERAGING INSIGHTS FOR EFFECTIVE CAMPAIGNS - Ari Kristiana; Melyana Ratana Pugu; Deswita (CV. Adiba Aisha Amira, 2024)
In addition to providing new tools, neuromarketing ushers in a new era of consumer behavior research. These discoveries have turned marketing from a guessing game into an art with strong neuroscientific foundations. Understanding the complexities of the consumer mind is made easier with the creative and powerful approach of neuromarketing. This innovative method paints a vivid picture of the feelings and ideas that influence consumers' choices. This inspires us to embrace the marketing of the future, in which data and intuition work together to provide more insightful understandings of customer behavior and, consequently, more successful marketing campaigns. The research was carried out using the literature study method. This research discusses the meaning of neuro- marketing, basic principles and techniques of neuro-marketing, understanding and factors that influence consumer behavior, methods of analyzing consumer behavior, neuro-scientific approaches in understanding consumer behavior, and integration of techniques, neuro- marketing with consumer behavior analysis